Case Report: Optical coherence tomography to guide PCI of iatrogenic injury of the circumflex artery after minimally invasive mitral valve repair - Borzanovic, Dusan; Ilic, Ivan; Nikolic, Dusan; Stojanovic, Ivan (Frontiers in Cardiovascular Medicine, 2023)
We present a case of a 42-year-old man with an iatrogenic injury of the left circumflex (Cx) coronary artery after mitral valve (MV) repair surgery. After suffering myocardial infarction without ST-segment elevation following minimally invasive MV surgery, repeated coronary angiography was done and we decided to perform optical coherence tomography (OCT), which revealed severe coronary stenosis of the dominant Cx caused by intramural hematoma. We proceeded with PCI and stent implantation.